Fenomena Prilaku Pelecehan Seksual Serta Akibatnya Dihubungkan Dengan Penanaman Moral Agama Keluarga - Suaidi (CV. ALIM'SPUBLISHING, 2023)
Instinctively every man and woman have mutual attraction. Attraction in the form of liking each other, loving each other and caring for each other, (Q.S. Al-Imron: 14). Apparently, love as a gift from Allah, SWT is sometimes channeled in ways that are contrary to religious teachings that are orderly and function to regulate human behavior. Sexual harassment has been widely discussed and has become a behavior that is published both through electronic and print media. Acts of sexual harassment will have a negative impact on the victim's psychology and traumatic in line with the development of the victim's soul. This study aims to find steps to anticipate the occurrence of sexual harassment behavior through education on a socio-religious approach. Sexual harassment is a deviant behavior due to high pressure of sexual desire while not being able to enter into marriage, channeling lust through sexual harassment has become a social disease that occurs everywhere, will result in prolonged traumatic consequences for the victim, which will lead to the destruction of the future of the victim of sexual harassment .